Developing Gestalt Counselling. - Mackewn, Jennifer (Developing Counselling series., 1997)
`In this eminently sensible, practical and thought-provoking book, Jennifer Mackewn takes gestalt light years forwards towards a synthesis and integration of psychological styles and away from what she describes as ""Perlism"". I agree with her: this is a book for therapists, not principally for gestaltists ... In inviting the reader to ""pick and choose"" from the many and varied, always practical, hands-on approach chapters ... Jennifer Mackewn hopes we will both enjoy her book and find it of use. This reader, commending the book to you all, has no doubt that both her hopes will be fulfilled'